Spanish Fund: subscriptions to 29th August, 1936
028-0015-001 SPANISH FUND. Subscriptions to 29th August, 1936. £ s. d. General Council 1000.0.0 Trade Unions 6204.13.10½ Trade Councils and Labour Parties 886.7.2 Individual and Other Subscriptions 2973.5.10½ Total Subscriptions received from British Sources 11064.6.11 Clothing Workers of America 995.10.0 International Ladies Garment Workers' Union, America, per Mr. Dubinsky 3972.13.9 TOTAL £16,032.10.8 292/946/28/15